All-Fiber and Calibration-Free Intrinsically Stable Polarization-Modulated Units for Measurement-Device-Independent Quantum Key Distribution - Yongjie Chen; Naida Mo; Jindong Wang; Jianling Yin; Tianming Zhao; Zhengjun Wei; Yafei Yu; Zhiming Zhang (IEEE Photonics Journal, 2023)
There are several groups have implemented polarization encoding measurement-device-independent quantum key distribution (MDI-QKD). However, these groups use manual polarization controller to achieve the initial polarization state for encoders, and some of the encoders cannot fully satisfy the two bases for polarization encoding quantum key distribution. Here, we apply an all-fiber and calibration-free intrinsically stable polarization-modulated unit (APMU), which can maintain stable encoding for several hours without any calibration. A proof-of-principle demonstration of MDI-QKD based on our APMU is implemented with the four-intensity decoy state protocol. The proposed APMU can realize stable MDI-QKD encoding and simplify the operation for Alice and Bob, which makes the polarization encoding MDI-QKD more practical.